Serum microRNAs as Biomarkers of Human Lymphocyte Activation in Health and Disease - de Candia, Paola; Torri, Anna; Pagani, Massimiliano; Abrignani, Sergio (Frontiers in Immunology, 2014)
Induction of the adaptive immune system is evaluated mostly by assessment of serum antibody titers and T lymphocyte responses in peripheral blood, although T and B cell activation occurs in lymphoid tissues. In recent years, the release of microRNAs (miRNAs) in the extra-cellular environment has been exploited to assess cell functions at distance via measurement of serum miRNAs. Also activated lymphocytes release a large amount of nano-sized vesicles (exosomes), containing miRNA, but there are still few data on whether this phenomenon is reflected in modulation of serum miRNAs. Interestingly, miRNA signatures of CD4+ T cell-derived exosomes are substantially different from intracellular miRNA signatures of the same cells. We have recently identified serum circulating miR-150 as a sensor of general lymphocyte activation and we strongly believe that the identification of miRNAs differentially released by specific CD4+ effector T cell subsets (Th1, Th2, Th17 and Treg) may work as serum biomarkers of their elicitation in lymphoid tissues but also in damaged tissues, thus providing pivotal information about the nature of immune responses occurring in health and disease.